THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) ASSISTED WITH AUDIO VISUAL MEDIA ON THE AFFECTIVE COMPETENCY OF STUDENTS ON SCIENCE LEARNING IN CLASS VII JUNIOR HIGH SCHOOL - Muhammad Yusuf; Nur Azizah; Lufri Lufri (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
Affective is one of the competencies that must be measured as part of successful learning. The achievement of this competency is influenced by several factors, such as the use of learning models and media. This study tries to reveal the effect of the STAD model assisted by audio-visual media on the attitude competence of students in science subjects in class VII junior high school. The method used is quasi experiment with purposive sampling. Data were collected through observation sheets and analysed using the Mann-Whitney U Test. The results revealed that learning in the experimental class showed better affective than the control class. So, it is concluded that the STAD model assisted by audio-visual media has a significant effect on the affective competence of students in science subjects.